Women in the Bible, Qumran, and early Rabbinic literature : their status and roles - Heger, Paul, 1924- (Studies on the Texts of the Desert of Judah, 2014)
Women in the Bible, Qumran and Early Rabbinic Literature: Their Status and Roles portrays the tension between the unity of husband and wife and their different legal and social status from a wide range of perspectives, as deduced from the texts of the three corpora. The volume discusses the related topics of divorce, polygamy, woman's obligations to fulfill precepts, membership in the community, genealogy and attitudes toward sex, such as rejection of asceticism. Women in the Bible, Qumran and Early Rabbinic Literature begins with an objective interpretation of the biblical narratives of the Creation and the Fall, the intellectual basis of Jewish attitudes toward women, and then analyzes the divergent interpretations of Qumran and the Rabbis, the grounds of their distinct doctrines and halakhot .